Breast health screening: a UK-wide questionnaire. Issue 1 (4th May 2021) - Jiwa, Natasha; Takats, Zoltan; Leff, Daniel R; Sutton, Christopher
Abstract : Background: Currently, there is an unmet clinical need in identifying and screening women at high risk of breast cancer, where tumours are often aggressive and treatment intervention is too late to prevent metastasis, recurrence and mortality. This has been brought into sharp focus by the SARS-CoV-2 global pandemic, constantly changing hospital policies and surgical guidelines in reducing access to established screening and treatment regimens. Nipple aspirate fluid (NAF), is thought to provide a unique window into the biological processes occurring within the breast, particularly in the context of a developing neoplasm. Evaluation of NAF in asymptomatic women, for novel chemical biomarkers of either early disease and/or cancer risk offers tremendous promise as a tool to facilitate early detection and to supplement screening. However, it is acceptability as a method of collection and screening by women is critical and yet unknown. A breast health questionnaire was disseminated to women through breast cancer charities, patient support groups and social media platforms, with the aim of collecting opinions on the acceptability of use of NAF as a potential screening tool. Method: Following ethical approval a questionnaire was prepared using online surveys consisting of four parts: (a) introduction on breast health screening in the UK, (b) core demographic data, (c) questions regarding screening and the acceptability of using NAF and (d) opinions about the process of collecting and using nipple fluid for screening. The voluntary and anonymous questionnaire was disseminated through social media, professional networks, charity websites and by individuals between October 2019 and December 2020. Survey responses were collected electronically, and the data analysed using online surveys statistical tools. Results: A total of 3178 women completed the questionnaire (65.9% Caucasian, 27.7% Asian/British Asian, 0.6% black and 5.0% other). Of these, 2650 women (83.4%) had no prior knowledge of NAF and 89.4% were unaware that NAF can be expressed in up to 90% of all women. Concerning their risk of breast cancer, 89.8% of women were keen to know their future risk of breast cancer, 8.5% were unsure whether they wanted to know their risk and a further, 1.6% did not want to know. Regarding screening, 944 women (29.8%) were unaware of the lack of routine National Health Service Breast Screening for those under the age of 47 years. Furthermore, 53.0% of women were unaware that mammographic screening is affected by breast density. In terms of the acceptability of home testing for breast health, 92.0% were keen to undergo a home test. Both 79.7% and 70.9% stated they would consider hand massage and a breast pump to acquire nipple fluid samples, respectively. A further 48.6% of women would consider the use of a hormonal nasal spray for the same purpose. However, with regards to acquiring results from NAF testing, 42.6% of women would prefer to receive results at home and 34.2% in a medical facility. Finally, 91.6% of women believed that breast health should be incorporated as part of school education curriculum. Conclusion: Public awareness regarding breast screening protocols and limitations of mammography could be improved. Many women were unaware that NAF might be a useful biofluid for future risk prediction, and yet the concept of self-testing of nipple fluid, with either hand massage or a breast pump was well received. Efforts should be made to increase awareness of the benefits of alternative and supplementary tests, especially in the context of high-risk individuals and younger patients.